(untitled) (Research, Society and Development, 2021)
The aim of the present study was to examine and highlight the effects of orthognathic surgery associated with alteration of the occlusal plane through the correlation of two case reports and a literature review. Through the use of electronic databases, a literature search was carried out, surveying the published studies, that was ilustrated through two case reports. Using surgical approaches, was possible to, basically, promote mandibular advancement and counterclockwise rotation of the occlusal plane in class II patients, even as the mandibular recoil movement with occlusal plane clockwise rotation in the case of a class III patient. All surgical management was carried out in order to create a stable and functional occlusal relationship for patients at a level that could not be reached only by conventional technique. In addition, the study is also applied as implications of this orthosurgical conduct in the tissue changes and facial profile of class II and class III patients, both with vertical excess of the maxilla. It was observed this type of orthosurgical treatment increases postoperative occlusal stability and produces satisfactory aesthetic results.